2017
DOI: 10.2136/sssaj2017.03.0093
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Manure Injection and Nitrification Inhibitors Impacts on Nitrous Oxide Emissions and Nitrogen Transformations in a Barley Crop

Abstract: Mitigating the greenhouse gas emissions that arise durin manure is a crucial environmental challenge. We evalu effects of liquid manure timing (fall vs. spring) and nitrifi [2-chloro-6-(trichloromethyl) pyridine (nitrapyrin) vs. 3 phosphate (DMpp)] on n 2 O emissions, soil mineral n ley (Hordeum vulgare L.) productivity, and n uptake. E established in an incomplete split-plot design in Laco AB, Canada. Repeated measurements included n 2 O flu chambers, and soil ammonium (nH 4 -n) and nitrate (nO Relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 35 publications
6
52
0
Order By: Relevance
“…These events preceded the start of the automated chamber measurements on DOY 102 and so could not be corroborated by them. However measurements with manual chambers earlier in spring 2015 by Lin et al (2018) indicated that N 2 O emission events occurred from DOY 85 to 100 that were similar in magnitude although not always in timing with those modelled (Fig. 4b).…”
Section: Fall Slurry Applicationsmentioning
confidence: 66%
See 4 more Smart Citations
“…These events preceded the start of the automated chamber measurements on DOY 102 and so could not be corroborated by them. However measurements with manual chambers earlier in spring 2015 by Lin et al (2018) indicated that N 2 O emission events occurred from DOY 85 to 100 that were similar in magnitude although not always in timing with those modelled (Fig. 4b).…”
Section: Fall Slurry Applicationsmentioning
confidence: 66%
“…Weather data (radiation, air temperature -T a , humidity, wind speed and precipitation) were recorded hourly from 2012 to 2016 at the South Campus Farm. During the first experimental year (16 September 2014 to 15 September 2015) T a remained 1-2 • C higher than historical (1981-2010) averages (Lin et al, 2018; Table 4). Precipitation was slightly higher than historical averages during autumn and winter but Year Date Management Amount was about one-half those during spring and summer.…”
Section: Site Description and Experimental Designmentioning
confidence: 69%
See 3 more Smart Citations